ANALISIS LAMA WAKTU PANGKAL BATANG TEBU (Saccharum officinarum L.) TERTINGGAL DI LAHAN TERHADAP NILAI RENDEMEN - Lusiana Antika; Pantja Siwi V R Ingesti (Universitas Tidar, 2020)
Sugar cane (Saccharum officinarum L) is the main commodity as raw material for sugar production. Therefore, agricultural land in Java must be able to meet the needs of sugar cane for PG. The common problem when harvesting sugar cane is the lack of cutting labor thus sugarcane felling is not carried out according to the provisions known as the land tight. As a result, the base of sugarcane stalks left long in the field. The base of the sugarcane stem is the rootstock where the yield value is high. This study on the analysis of duration of sugarcane stumps left in the land due to landless cutting is a case study conducted in the Ngadirejo PG area, Kediri Regency. In this study, the variable used is the time spent by the stump of sugarcane left in the field after cutting. Based on the observations at the location of sugarcane harvest, it can be seen that the length of sugarcane stumps remaining in the land was between 6 cm-15 cm, with an average weight of 0.07 kg - 0.3 kg. In the laboratory test, the yield value for the variable after felling was 9.85 immediately, 8.98 at 2 days after harvest, and 4.83 after 14 days. Thus it can be concluded that the longer the base of sugarcane sticks left on the ground the lower the yield value is.